Attitude and perception towards vaccination against poliomyelitis in Peshawar, Pakistan - Shafique, Farheen; ul Hassan, Mahreen; Nayab, Hina; Asim, Noreen; Akbar, Nazia; Shafi, Nuzhat; Manzoor, Sadaf; van Eeden, Freek; Ali, Shaukat (Revista de Saúde Pública, 2021)
OBJECTIVE: This research aimed to quantitatively assess the general public's awareness, attitude and perception of polio and its vaccination in Peshawar KPK, Pakistan. METHODS: We conducted a survey-based study to understand the surge in polio cases from 2015 to 2019 in the Peshawar city of the Khyber Pakhtunkhwa (KPK), Pakistan. A pre-tested questionnaire-based study was conducted in 2019 to assess the attitude and general perception of residents of Peshawar KPK towards polio vaccination. RESULTS: Out of 241 country-wide polio cases, 63 (26.1%) polio cases were reported in Peshawar city from 2015–2019. The questionnaire revealed that individuals between 18–30 years of age had sufficient knowledge (65.1%) about polio. Male and female participants had equal awareness ( 43%). Participants with higher education (45.9%), those with better financial status (49.5%), individuals with children < 5 years of age (46.4%), and those who had experience of a polio patient (63.1%) had better knowledge. Participants inhabiting the central city were better aware (50.5%) of polio than individuals living in the outskirts. CONCLUSION: The data indicated that poor knowledge and negative attitudes of people towards polio vaccination are the main causes of the polio eradication program's failure. Moreover, religious beliefs, unchecked migration between the Pak-Afghan border, and lack of knowledge about polio vaccination are identified as critical barriers to polio eradication.